Communicating Sufi Teachings in 21st Century: A Study of “Muslim Institute” Sufi Order in Pakistan - Anbreen Yasin Khan; Rachmah Ida; Muhammad Rehan Shaikh (Jurnal Komunikasi Islam, 2022)
This paper reports on research conducted with Muslim Institute of Hadrat Sultan Bahoo order in Pakistan. Using a qualitative approach and Manuel Castells' theory of the network society, the findings illustrate that respondents recognize the role of digital media to increase the outreach of Sufi messages. The leaders of the institute realize the evils of the digital era and suggest spiritual solutions. However, although the use of the modern mode of communication increases access, live events have greater value and a strong impact.